DESENVOLVIMENTO DE METODOLOGIA DE COLETA E MANUTENÇÃO EM LABORATÓRIO DA FORMIGA INVASORA PARATRECHINA LONGICORNIS LATREILLE (HYMENOPTERA: FORMICIDAE) - Solis, D.r. [UNESP]; Bueno, O.c. [UNESP]; Moretti, T.c. [UNESP] (Instituto Biológico, 2021)
The genus Paratrechina is a cosmopolitan group, with some species invading residences and hospitals. In Brazil, the most important species are:Paratrechina fulva andParatrechina longicornis. In spite of the importance of these species as urban pests, there is a lack of information on their biology, since studies on urban ants are rather recent in our country and also due to the difficulty of keeping colonies of P. longicornis in the laboratory. Therefore, the present study was aimed at developing two methodologies: one suitable for collecting and another for keeping colonies of P. longicornis in the laboratory. Concerning the collections, four methodologies were analyzed, while for keeping colonies in the laboratory, the types of containers where the colonies would be stored as well as the food items that would comprise their diet were evaluated. The most adequate methodology for collecting was the one performed using an entomological aspirator. Regarding the maintenance of colonies, the most adequate container was the test tube with cotton steeped in water, while in the tests on food attractiveness, the workers showed preference for sugary liquids and dead insects, mainly termites. Moreover, two infestations of mites from the families Acaridae, Macrochelidae (genus Macrocheles) and Uropodidae in the colonies of P. longicornis have occurred, which caused a significant mortality of the colonies, due to an unbalance in the social behavior of the ants.

O gênero Paratrechinaé um grupo cosmopolita, com algumas espécies invadindo residências e hospitais. No Brasil, as espécies mais importantes são: Paratrechina fulva e Paratrechina longicornis. Apesar do destaque como pragas urbanas, há uma escassez de informações sobre sua biologia, devido às pesquisas com as formigas urbanas serem recentes em nosso país e pela dificuldade na manutenção de P. longicornis em laboratório. Assim, este estudo pretendeu desenvolver uma metodologia adequada de coleta e outra para a manutenção em laboratório de P. longicornis. Para as coletas foram analisadas quatro metodologias, enquanto para a manutenção em laboratório foram avaliados: os tipos de recipientes onde as colônias permaneceriam alojadas e os itens alimentares que comporiam a dieta. Nas coletas das colônias a metodologia mais adequada foi aquela em que se utilizou o aspirador entomológico. Na manutenção das colônias, o recipiente mais adequado foi o tubo de ensaio com algodão embebido em água e, quanto aos testes de atratividade alimentar, as operárias têm preferências por líquidos açucarados e por insetos mortos, principalmente cupins. Além disso, ocorreram duas infestações por ácaros das famílias Acaridae, Macrochelidae (gênero Macrocheles) e Uropodidae nas colônias de P. longicornis, que ocasionaram uma significativa mortalidade das colônias, devido a um desequilíbrio no comportamento social.
DEVELOPMENT OF A METHODOLOGY OF COLLECTION AND REARING OF THE INVASIVE ANT PARATRECHINA LONGICORNIS LATREILLE (HYMENOPTERA: FORMICIDAE) IN THE LABORATORY
Keywords: Formicinae; tramp species; crazy ant; mites; feeding; Formicinae; formigas urbanas; formiga louca; ácaros; alimentação